UMP staff need to manage their finances wisely - Siti Nurfarmy, Ibrahim (2021)
PEKAN, 12 July 2021 - The implementation of moratorium 2.0 announced by the government on 7 July is a wise step taken to reduce the burden of the people as well as to continue to survive.